Genelogi Gerakan Pembaruan Islam - ., Mariyani; Jufri, Muhammad; Amin, M. (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The history of Islamic development is a dynamc one involving phases of brilliant progress and periods of significant decline. These conditions of decline triggered the birth of the renewal movement (tajdid) as an effort to revitalize the community ini respondinh to the challenges of the times. This article examines the genealogy of the Islamic renewal movement by tracing its historial roots from the classical period to the modern era. The study focuses on how renewal functioned as an instrument of revitalization through the mechanisms of ijtihad and adaptation to modernity and western colonialism. This investigation also highlights the contributions of global thinkers such as Jamaluddin Al-Afghani and Muhammad Abduh, as well as local Indonesian figures Such as Ahmad Dahlan and Hasyim Asy’ari. The analysis shows that the renewal movement is not an aberration, but rather an integral intellectual tradition within Islam that maintans the relevance of teachings amidst ever-evolving global change.